APPLICATION OF THE MATURITY LEVEL MODEL IN THE PLAN AND ORGANISE (PO) DOMAIN USING THE COBIT 4.1 FRAMEWORK FOR INFORMATION TECHNOLOGY GOVERNANCE - Sutri Pahdianingsi; Nofriadi; Wiwin Handoko (Informatika, Universitas Jenderal Soedirman, 2022)
Management on human resource management at Wira Husada General Hospital for services in IT currently needs to be audited for the development of current IT performance that is in line with management expectations or not regarding the information system. If an IT audit is not carried out, it will affect accreditation, service satisfaction and the development of information systems. As for examples of previous research, namely the case study of the ARS Bandung University which applied COBIT 4.1 to conduct audits of academic information systems. The purpose of research at RSU Wira Husada is to build an IT governance support application system that provides maturity level services for the HR department using the COBIT 4.1 framework method that focuses on the web-based Plan and Organize (PO) domain. This research method was carried out by filling out a questionnaire assessment by the respondents then processed using the COBIT formula and calculating the value of the maturity level. The results showed that currently Wira Husada RSU was at a managed and measurable level with a maturity level of 3.96. This study concludes that RSU Wira Husada currently has implemented a planning and organizing framework at the managed level.